2003
DOI: 10.1182/blood-2002-09-2955
|View full text |Cite
|
Sign up to set email alerts
|

Allografting with nonmyeloablative conditioning following cytoreductive autografts for the treatment of patients with multiple myeloma

Abstract: The full potential of a graft-versus-myeloma effect after allogeneic hemato-poietic cell transplantation (HCT) for patients with multiple myeloma (MM) has not been realized because of excessive early transplantation-related mortality (TRM) with conventional HCT. Autolo-gous HCTs have been characterized by almost universal disease recurrences. The current trial combined autologous HCT with subsequent nonmyeloablative alloge-neic HCT to maintain the benefits of both approaches with acceptable toxicity. Fifty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
261
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(282 citation statements)
references
References 58 publications
13
261
1
7
Order By: Relevance
“…Maloney et al [14] also demonstrated that 5 patients achieved CR after 9 months from RICT without any GVHD, suggesting that subclinical GVHD or another antitumor effect of this approach may control multiple myeloma. Badros et al [20] treated 31 patients who had had 1 or 2 prior autografts with transplants from identical sibling donors (25 patients) or unrelated donors (6 patients).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Maloney et al [14] also demonstrated that 5 patients achieved CR after 9 months from RICT without any GVHD, suggesting that subclinical GVHD or another antitumor effect of this approach may control multiple myeloma. Badros et al [20] treated 31 patients who had had 1 or 2 prior autografts with transplants from identical sibling donors (25 patients) or unrelated donors (6 patients).…”
Section: Discussionmentioning
confidence: 98%
“…In the series of Maloney et al [14], 48% of the patients had received more than one treatment regimen, and the median time between diagnosis and APBSCT was 282 days. In the Kro¨ger et al [13] study of tandem auto-miniallotransplant protocol, the median time from diagnosis to autotransplantation was 13 months.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Four patients developed severe acute GVHD (grades 3-4), and chronic GVHD developed in 60%. [20] With a median follow-up of 60 months after allograft, the survival at 60 months was 69%, and the progression-free survival 40%.…”
Section: Non-ablative Allogeneic Transplantsmentioning
confidence: 96%
“…Conversely, complete response rates and early survivals were very good when a planned tandem reduced-intensity allograft approach was utilized as part of the initial treatment. [20,[27][28][29] In one study the anti-CD52 antibody alemtuzumab was added to total body irradiation and fludarabine in 20 patients with multiple myeloma undergoing reduced-intensity allografting as part of front-line therapy.[30] Fourteen of the 20 patients were given donor lymphocyte infusions post-transplant for residual or progressive disease. Although transplant mortality and survival at 2 years were acceptable at 15% and 71%, respectively, the complete response rate of 10% was disappointing.…”
mentioning
confidence: 99%